The identity and significance of the high-latitude Early Ordovician Mediterranean brachiopod Province. (12th December 2021) - Cocks, L. Robin M.; Popov, Leonid E.
Abstract: During the Early Ordovician Epoch, the Mediterranean brachiopod Province was extensive in the higher-latitude sectors of the globe in the Southern Hemisphere. The latter was much occupied by the massive continent of Gondwana, which stretched from north of the Equator S-wards to cover the South Pole. The Mediterranean Province can be separated into two groups: Group 1, the higher-latitude fauna dominated by large linguliform brachiopods; and Group 2, which is more diverse, particularly in orthides. The large linguliform brachiopod faunas are particularly well known in southern Europe (France, Spain and Bohemia) and North Africa, and the second group in Avalonia, Chile and Argentina. The province is different from, but merges with, more diverse contemporary faunas in the lower latitudes of Gondwana to its north, although the latter contrast with other lower-latitude faunal provinces in South China, Laurentia, Siberia and elsewhere. Since the Rheic Ocean between Avalonia and Gondwana was relatively narrow during the Early Ordovician Epoch, the Avalonian brachiopods were integral parts of the Mediterranean Province, but only until end of the Dapingian Age. This paper focuses on the earlier phases of the Mediterranean Province, although the province continued until near the end of the Ordovician Period. Intermediate-latitude Baltica and some other faunas are included in new principal components and other analyses in order to compare them with the Mediterranean Province faunas. Radiation was very significant for many brachiopod taxa during the period, with first appearances of the Plectambonitoidea (Taffiidae), several orthide families (Euorthisinidae, Tarfayidae and Anamalorthidae) and the earliest endopunctate orthide, the dalmanelloid Lipanorthis.